An Analysis of Medical Students’ Learning Experiences in Small Group-Based Teaching in Kurdistan Region-Iraq - Ali Abdi, Mahmoud; Mikhail, Dilveen; Abdi, Basheer; Mustafa, Dastan; Ibrahim, Sawen (Journal of Contemporary Medical Sciences, 2024)
Objective: This study aims to evaluate the learning styles, activities, and experiences of medical students within the context of small groupbased teaching in the Kurdistan Region of Iraq. Methods: A cross-sectional study was conducted between February and May 2022 at Zakho College of Medicine, involving students from various medical colleges in the region. A pre-designed questionnaire was administered both in-person and online. Comprising two main parts in addition to demographic information, the questionnaire assessed students' learning styles based on O'Brien's modality learning channel preference and their preferences and experiences in small-group settings. Results: The sample included students from the 1st to the 5th stage, totaling around 400 participants. The cohort was predominantly female (60.05%) and largely from the 2nd stage of medical education (55.03%). Visual Learning was the most common learning style, particularly among female students. Significant variations in learning styles were noted across different academic stages and universities. Small-group activities and formative assessments were generally favored. While most students were either "satisfied" or found it "natural" concerning group size, dissatisfaction was prominent regarding available teaching resources. Statistical analyses confirmed significant differences in learning styles, preferred teaching methods, and feelings about the learning environment. Conclusion: The study offers critical insights into the diverse learning preferences and experiences of medical students in small-group settings. Despite a general preference for Visual Learning and small-group activities, significant variations exist, warranting a nuanced approach to educational strategy. Given the diverse learning preferences and significant dissatisfaction with available resources, a multifaceted educational approach is recommended, including diverse teaching and assessment methods and increased investment in teaching resources.